2015
DOI: 10.1007/s10571-015-0244-0
|View full text |Cite
|
Sign up to set email alerts
|

Sigma-1 Receptor Modulates Neuroinflammation After Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) remains a significant clinical problem and contributes to one-third of all injury-related deaths. Activated microglia-mediated inflammatory response is a distinct characteristic underlying pathophysiology of TBI. Here, we evaluated the effect and possible mechanisms of the selective Sigma-1 receptor agonist 2-(4-morpholinethyl)-1-phenylcyclohexanecarboxylate (PRE-084) in mice TBI model. A single intraperitoneal injection 10 μg/g PRE-084, given 15 min after TBI significantly reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 37 publications
(39 reference statements)
4
30
0
3
Order By: Relevance
“…Both S1R and BDNF were present in BV-2 microglial cells, yet treating these cells with an S1R agonist did not facilitate BDNF secretion. Although activated microglia (Nakajima et al, 2001; Sun et al, 2014), including a murine N9 microglial cell line (Gomes et al, 2013), are capable of secreting BDNF, our finding is in agreement with numerous studies indicating that the S1R is present in microglia and can modulate injury or toxicant-induced microgliosis by various mechanisms not involving BDNF (Behensky et al, 2013; Cuevas et al, 2011; Dong et al, 2015; Gekker et al, 2006; Hall et al, 2009; Mancuso et al, 2012; Moritz et al, 2015; Robson et al, 2013; Wegleiter et al, 2014; Wu et al, 2015; Zhao et al, 2014). Alternatively, the BV-2 cell line may lack the necessary machinery for investigating S1R-BDNF interactions in microglia or the microglia may need to be activated in order to study the effect.…”
Section: Discussionsupporting
confidence: 91%
“…Both S1R and BDNF were present in BV-2 microglial cells, yet treating these cells with an S1R agonist did not facilitate BDNF secretion. Although activated microglia (Nakajima et al, 2001; Sun et al, 2014), including a murine N9 microglial cell line (Gomes et al, 2013), are capable of secreting BDNF, our finding is in agreement with numerous studies indicating that the S1R is present in microglia and can modulate injury or toxicant-induced microgliosis by various mechanisms not involving BDNF (Behensky et al, 2013; Cuevas et al, 2011; Dong et al, 2015; Gekker et al, 2006; Hall et al, 2009; Mancuso et al, 2012; Moritz et al, 2015; Robson et al, 2013; Wegleiter et al, 2014; Wu et al, 2015; Zhao et al, 2014). Alternatively, the BV-2 cell line may lack the necessary machinery for investigating S1R-BDNF interactions in microglia or the microglia may need to be activated in order to study the effect.…”
Section: Discussionsupporting
confidence: 91%
“…However, when Sig-1R expression was knocked out, treatment with PRE-084 did not have any restorative effects on mice, which indicated that Sig-1R regulated inflammation (Francardo et al 2014). Consistent with previous studies, Dong et al found that PRE-084 could reduce microglial activation and nitrosative and oxidative stress to proteins after TBI (Dong et al 2016). SKF83959 (3-methyl-6-chloro-7,8-hydroxy-1-[3-methylphenyl]-2,3,4,5-tetrahydro-1H-3-benzazepine), an atypical dopamine receptor-1 agonist, can enhance the activity of endogenous dehydroepiandrosterone (DHEA) in a synergistic manner and inhibit the activation of BV2 microglia and the expression/release of proinflammatory cytokines (Wu et al 2015).…”
Section: Cell Mol Neurobiolsupporting
confidence: 70%
“…Another study demonstrated that Sig1-R may promote cell survival via the regulation of ER stress, p38 MAPK activation, ROS production, and proteins involved in apoptosis (Caspases-3, Bax) in breast cancer cells (Happy et al 2015). In a TBI model, Dong et al found that PRE-084 can significantly reduce lesion volume, lessen brain edema, and accelerate the recovery of nerve function and body weight after TBI, which indicated that MAMs may play an important role in cell fate and neural function following TBI (Dong et al 2016). …”
Section: Sig1-rmentioning
confidence: 99%
See 1 more Smart Citation
“…The sigma agonists DTG (1,3-di-(2-tolyl)guanidine) and afobazole have also been shown to suppress microglial activation and migration and the release of inflammatory cytokines in response to not only LPS, but also other microglial activators such as ATP, uridine triphosphate and monocyte chemoattractant protein-1 [100]. In an in vivo model of traumatic brain injury, the sigma-1 agonist PRE084 has been shown to reduce IBA-1 expression following controlled cortical impact in association with reduced lesion volume and improved behavior in mice [101]. Similarly, PRE084 also reduced counts of IBA-1 positive microglial cells in a mouse model of ALS [24].…”
Section: 3 Sigma-1 Receptor Mediated Mechanisms Of Neuroprotectionmentioning
confidence: 99%